TECHNIQUES OF TRANSLATIONS FOUND IN SOME FOOD AND BEVERAGE PACKAGINGS - Kadek Yogi Pratama; Made Susini; Dewa Ayu Dyah Pertiwi Putri (Universitas Warmadewa, 2024)
This research was to find out the types of translation techniques and the most dominant type of translation technique by the translator in some food and beverage packagings. The theory of translation techniques by Molina (1998) was used as a basic theory. This research used qualitative and quantitative method to explain the results of the analysis of the types of translation techniques and to calculate what type of translation technique is dominant to be used. The data source which was used in this research was food and beverage packaging. The data were collected by finding the food and beverage products in the various super markets. The information, sentences, phrases or words in the packaging were collected by taking a picture. The English texts were compared with the Indonesian ones and classified based on their types of translation techniques. The data were analyzed descriptively using the theory of translation techniques. After data were analyzed, they were calculated to find what type of translation technique was dominant to be used in food and beverage packaging. The result of this research showed that translation techniques used in translating the words, expressions, sentences and information that contained in food and beverage packaging were literal, borrowing, amplification, description, reduction, and calque. The most dominant type of translation technique applied is borrowing technique with 37 data (37%) found.